Vladimir Bibikhin: His Biographical Notes and the Moscow Circle of Religious Intellectuals - Stoeckl, Kristina (Stasis, 2015)
This article is a reading of Vladimir Bibikhin’s biographical notes and offers a sketch of the dynamics among the Moscow circle of religious intellectuals during the last decades of the Soviet Union and later. Bibikhin’s personal testimony and philosophical work offer an example of how the tradition of prerevolutionary religious philosophy, Orthodox thought, and critical philosophy, survived Soviet suppression and censorship, and emerged to new life after the fall of communism. Bibikhin also reminds us that Russian religious thinkers were often read in support of Russian nationalism and he was deeply critical of this trend.